DLP 3D printing slurry, porous scaffold as well as preparation method and application of porous scaffold

By introducing copper-containing bioactive glass and vacuum centrifugal treatment in the DLP 3D printed slurry, the problem of insufficient quality and purity of porous scaffolds in the prior art is solved, high-quality porous scaffold preparation is achieved, and cell osteogenesis ability is promoted.

CN119564925APending Publication Date: 2025-03-07SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411791418.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing DLP 3D printing technology needs to improve quality and purity when preparing bone stents, and conventional bioactive glasses have limited osteogenic capabilities.

Method used

Provide a DLP 3D printing slurry containing 10%~70% copper bioactive glass, 26.7%~87% photosensitive resin, 0.3%~1% photoinitiator, 2%~3% dispersant, and 2%~3%. The bubbles are removed by vacuum centrifugation, and the porous scaffold is printed using DLP 3D printing technology, and sintered at 500~850 ℃.

Benefits of technology

It improves the quality and purity of the porous scaffold, promotes the expression of cell osteogenesis-related genes, enhances the ability to promote bone, and has low toxicity, and is suitable for bone repair materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119564925A_ABST
    Figure CN119564925A_ABST
Patent Text Reader

Abstract

The invention provides DLP 3D printing slurry, a porous scaffold and a preparation method and application of the DLP 3D printing slurry and the porous scaffold, and the DLP 3D printing slurry is prepared from, by mass, 10%-70% of copper-containing bioactive glass, 26.7%-87% of photosensitive resin, 0.3%-1% of a photoinitiator and 2%-3% of a dispersing agent. The preparation method comprises the following steps: (1) uniformly mixing the photoinitiator, the photosensitive resin, the copper-containing bioactive glass and the dispersing agent to obtain a mixed solution; and (2) the mixed solution is subjected to vacuum centrifugal treatment, and the DLP 3D printing slurry is obtained. According to the invention, the quality and purity of the porous scaffold are improved, the expression of cell osteogenesis related genes can be promoted, and the osteogenesis promoting capability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a DLP 3D printing slurry, a porous scaffold, and a preparation method and application thereof. Background Art

[0002] There are two common methods for manufacturing porous scaffolds: template method and 3D printing technology. Template method can only manufacture scaffolds with simple shapes, but bone scaffolds are generally porous. Traditional template method is usually difficult to control the size, geometry and interconnectivity of the pores, and one structure requires a corresponding mold, which is very expensive and not easy to adjust the fine structure, and cannot meet actual needs. The emerging 3D printing technology has brought good news to the medical field. 3D printing technology can accurately design the appearance and internal microstructure of the scaffold. At present, the most commonly used 3D printing technologies for preparing scaffolds with composite materials as raw materials include fused deposition modeling (FDM), selective laser sintering (SLS) and digital light processing (DLP). FDM is the most widely used 3D printing manufacturing technology, including three processes of feeding, melt extrusion and deposition molding. The scaffolds manufactured by FDM have good structural and mechanical properties. The main advantages of FDM are low cost, no use of organic solvents, and flexible methods for manufacturing interconnected porous structures, but FDM printing requires high temperature extrusion of materials and cannot print components such as cells or proteins. Compared with other technologies, the resolution of FDM is relatively low, at 100-150 μm, which has certain limitations when applied to brackets with high precision requirements.

[0003] SLS selectively heats powder particles through laser energy, and the melted particles then solidify and fuse to form a 3D structure. The SLS system consists of three main components, namely the spreading platform, the powder bed, and the laser system. SLS technology has many advantages in printing preparation. Compared with other methods, the SLS method does not require solvents, has a faster printing speed, and can be used for the preparation of large and complex structures. However, since high-temperature sintering is required during the preparation process of this technology, it cannot be used for cells and temperature-sensitive biological materials. SLS builds layer by layer by laser sintering the substrate according to the designed printing path. Its accuracy is higher than FDM, with a resolution of 50~100 μm. The only prerequisite for this method is that the material components are thermoplastic and thermally stable. Only approved thermoplastic excipients and polymers can be used in the SLS process.

[0004] DLP is a technology that uses photopolymerization for 3D printing, in which photosensitive resins are cured by absorbing light-induced photopolymerization. Photopolymerization causes the pattern within the resin layer to solidify. In DLP 3D printing, this principle is repeated layer by layer to solidify the resin and form each layer of the product. The thickness of the layer is controlled by the energy of the light source and the exposure time. DLP has high precision, with a general resolution of less than 50 μm, and can produce brackets with precise internal architecture and geometry.

[0005] Therefore, DLP has become a common method for preparing bone scaffolds. However, the quality of bone scaffolds prepared by DLP still needs to be improved, and the conventional bioactive glass used in bone scaffolds also needs to be further improved in terms of bone formation ability. Summary of the invention

[0006] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a DLP 3D printing slurry, a porous scaffold and a preparation method and application thereof, which improve the quality and purity of the porous scaffold, and can help promote the expression of cell osteogenesis-related genes and improve the osteogenesis ability.

[0007] The present invention is achieved through the following technical solutions: The present invention provides a DLP 3D printing slurry. Calculated by mass percentage, the DLP 3D printing slurry comprises: 10% to 70% copper-containing bioactive glass, 26.7% to 87% photosensitive resin, 0.3% to 1% photoinitiator, and 2% to 3% dispersant.

[0008] Preferably, the copper-containing bioactive glass is a copper-containing borosilicate bioactive glass; in terms of molar percentage, the proportion of copper in the copper-containing borosilicate bioactive glass is 0.1% to 1%.

[0009] Preferably, the photosensitive resin is trimethyl isopropyl phenol vinyl ester.

[0010] Preferably, the viscosity of the DLP 3D printing slurry is 2-10 Pa·s.

[0011] The present invention also provides a method for preparing the DLP 3D printing slurry, comprising: (1) uniformly mixing a photoinitiator, a photosensitive resin, a copper-containing bioactive glass and a dispersant to obtain a mixed solution; (2) The mixed liquid is subjected to vacuum centrifugation to obtain DLP 3D printing slurry.

[0012] Preferably, the vacuum centrifugation treatment time is 10 to 120 s.

[0013] The present invention also provides a porous bracket, wherein the porous bracket is printed using the DLP 3D printing slurry as described above as a raw material and a DLP 3D printing method.

[0014] The method for preparing the porous scaffold of the present invention comprises the following steps: (1) setting DLP 3D printing parameters, and forming the DLP 3D printing slurry by DLP 3D printing to obtain a bracket blank; (2) Sinter the scaffold blank at 500-850 °C to obtain a porous scaffold.

[0015] Preferably, in the method for preparing the porous scaffold, in step (2), the sintering procedure is: heating to 280-320 °C at a rate of 1.8-2.2 °C / min, continuing to heat to 500-850 °C at a rate of 0.8-1.2 °C / min, keeping the temperature for 80-100 min, and then cooling to 280-320 °C at a rate of 0.8-1.2 °C / min.

[0016] The present invention also provides application of the porous scaffold in preparing bone repair materials.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The DLP 3D printing slurry provided by the present invention has photosensitive properties and can be quickly cured under ultraviolet light, so that porous scaffolds can be printed through DLP printing technology. The DLP 3D printing slurry uses copper-containing bioactive glass organisms as the main raw material. The bioactive glass has good biocompatibility, and the porous scaffolds prepared based on the printing slurry have low toxicity. More importantly, the use of copper-containing bioactive glass organisms in the present invention introduces copper ions into the DLP 3D printing slurry. Copper ions help promote the expression of cell osteogenesis-related genes, promote local vascularization and regulate inflammation to achieve osteogenesis regeneration, and have a certain promoting effect on bone repair. In addition, the DLP 3D printing slurry of the present invention has a simple formula and stable performance, and the viscosity of the slurry is suitable for DLP 3D continuous printing.

[0018] In the preparation method of the DLP 3D printing slurry of the present invention, a vacuum centrifugal treatment method is adopted, that is, a method of combining dispersion and vacuuming by a centrifuge is used to achieve the purpose of defoaming, which makes it easier to remove bubbles in the slurry and improve the uniformity of the printing ink. At the same time, the use of a defoaming agent can be avoided, thereby improving the quality and purity of the porous scaffold.

[0019] The porous scaffold of the present invention is obtained by DLP 3D printing technology based on the DLP 3D printing slurry as described above. DLP 3D printing technology is a relatively fast printing technology that can produce scaffolds with precise internal structures and geometric shapes. Therefore, the present invention can obtain high-precision porous scaffolds based on DLP 3D printing technology. In addition, the porous scaffold of the present invention contains copper elements, which help promote the expression of cell osteogenesis-related genes, promote local vascularization and regulate inflammation to achieve osteogenesis regeneration, and have a certain promoting effect on bone repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 TG and DTG curves of the green body support in the embodiment of the present invention; Figure 2 The sintering process of the porous support in the embodiment of the present invention; Figure 3 The scanning electron microscope (SEM) images of the porous scaffold before and after sintering in the embodiment of the present invention; Figure 4 The mechanical test results of the porous scaffold in the embodiment of the present invention; Figure 5 The cytotoxicity of hBMSCs after co-culture with the extract of the porous scaffold in the embodiment of the present invention for 24 hours; Figure 6 The expression of ALPL, COL1A1 and Runx2 in hBMSCs after culturing for 14 days under the condition of 16-fold dilution of different porous scaffold extracts. 、 Ocn, Opn and Sp7 gene expression levels. DETAILED DESCRIPTION

[0022] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0023] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0024] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0025] The DLP 3D printing slurry of the present invention comprises, by mass percentage, 10% to 70% of copper-containing bioactive glass, 26.7% to 87% of photosensitive resin, 0.3% to 1% of photoinitiator, and 2% to 3% of dispersant.

[0026] The present invention introduces copper elements into the DLP 3D printing slurry, which helps to promote the expression of cell osteogenesis-related genes, promote local vascularization and regulate inflammation to achieve osteogenesis regeneration, and has a certain promoting effect on bone repair.

[0027] In terms of molar percentage, the proportion of copper in the copper-containing bioactive glass is 0.1% to 1%, and more preferably 0.5% to 1%. Within the scope defined by the present invention, as the amount of copper added increases, the effect of the prepared porous scaffold on promoting the expression of cell osteogenesis-related genes is enhanced.

[0028] The copper-containing bioactive glass of the present invention preferably adopts copper-containing borosilicate bioactive glass, and its composition is, by molar percentage, 3% to 4% Na2O, 5% to 8% K2O, 8% to 12% MgO, 12% to 15% CaO, 4% to 6% SrO, 20% to 23% SiO2, 35% to 40% B2O3, 1% to 3% P2O5, and 0.1% to 1% CuO. The particle size of the copper-containing bioactive glass is 5 to 60 μm, more preferably 40 to 60 μm.

[0029] The photosensitive resin of the present invention preferably uses trimethyl isopropyl phenol vinyl ester (TMPTA), the photoinitiator preferably uses 819 photoinitiator, and the dispersant preferably uses VOK-Disper 85000. Under light conditions, TMPTA can quickly undergo polymerization reaction, so that the photosensitive resin can be cured in a short time. Compared with the traditional thermal curing method, the light curing method does not require heating, thereby reducing energy consumption and production costs. TMPTA can be cured at a lower temperature, further improving production efficiency.

[0030] The present invention can obtain a slurry with suitable viscosity and suitable for continuous DLP 3D printing by controlling the ratio of each substance in the slurry. Specifically, the viscosity of the DLP 3D printing slurry is 2-10 Pa·s, and more preferably 3-8 Pa·s.

[0031] The DLP 3D printing slurry provided by the present invention has a simple formula, has photosensitive properties, and can be quickly cured under ultraviolet light. By adjusting the mass ratio of copper-containing bioactive glass, photosensitive resin, photoinitiator and dispersant in the printing slurry, a 3D printing slurry that is evenly dispersed and suitable for continuous DLP printing can be obtained.

[0032] The preparation method of the DLP 3D printing slurry of the present invention is: (1) Preparing a copper-containing bioactive glass / photosensitive resin mixed solution: uniformly mix a photoinitiator, a photosensitive resin, a copper-containing bioactive glass and a dispersant to obtain a copper-containing bioactive glass / photosensitive resin mixed solution.

[0033] (2) The copper-containing bioactive glass / photosensitive resin mixed solution is vacuum centrifuged in a vacuum centrifuge for 10 to 120 seconds to obtain a DLP 3D printing slurry that is evenly mixed and free of bubbles.

[0034] The presence of bubbles in the printing slurry will interfere with the jetting of the print head, resulting in unstable size and shape of ink droplets, thereby affecting the printing accuracy. Bubbles may also form defects such as bubble holes and foam spots during the printing process, which will destroy the overall aesthetics of the printed product. To this end, the present invention uses a vacuum centrifugal method to process the slurry, that is, to remove bubbles by combining dispersion and vacuuming by a centrifuge, which can avoid the use of defoaming agents, make it easier to remove bubbles in the slurry, and improve the quality of the porous scaffold printed subsequently.

[0035] Preferably, the homogenization speed of the vacuum centrifuge used in the present invention is 500-2000 rpm.

[0036] The DLP 3D printing slurry is used as a raw material to perform DLP 3D printing to obtain a porous scaffold. The specific method includes the following steps: (1) DLP 3D printing parameters are set, and the DLP 3D printing slurry is formed by DLP 3D printing to obtain a porous bracket blank.

[0037] (2) After the porous scaffold green body is sintered at a high temperature, the photosensitive resin, the photoinitiator and the dispersant are removed to obtain a porous scaffold.

[0038] The present invention uses DLP 3D printing technology to adjust the pore size, porosity, connectivity, side pores, etc. of the porous scaffold to obtain a desired personalized porous scaffold. In the present invention, the personalized porous scaffold is a regular geometric body and other irregular three-dimensional porous structures, preferably a regular geometric body, such as a cuboid, a cube, a cylinder, etc., but not limited thereto.

[0039] The parameters of the DLP 3D printing of the present invention include: light intensity of 10000 μW, scraper displacement speed of 100 mm / s, layer-by-layer curing time of 10-20 s, layer spacing of 0.5 mm, and layer height of 0.05-0.1 mm.

[0040] The porous scaffold obtained by the present invention has a porosity of 50% to 75%, a pore connectivity of 95% to 99.96%, and a pore size (including side pores) of 300 to 600 μm.

[0041] The sintering temperature used in the present invention is preferably 500-850°C, and the sintering procedure is: heating to 280-320°C at a rate of 1.8-2.2°C / min, continuing to heat to 500-850°C at a rate of 0.8-1.2°C / min, keeping warm for 80-100 min, and then cooling to 280-320°C at a rate of 0.8-1.2°C / min.

[0042] In a specific embodiment, the sintering procedure is as follows: first, the temperature is raised to 300°C at a rate of 2°C / min, then the temperature is further raised to 500°C at a rate of 1°C / min, then the temperature is kept at that temperature for 90 minutes, the temperature is sequentially lowered to 300°C at a rate of 1°C / min, and then naturally cooled to room temperature.

[0043] The manufacturing method of the porous scaffold is low-cost, relies on the high designability of DLP 3D printing technology, is highly practical, and can be used as a bone repair material.

[0044] Example 1: Preparation of DLP 3D printing slurry containing 10% copper borosilicate bioactive glass by mass Preparation of copper-containing borosilicate bioactive glass: 6 mol% Na2O, 8 mol% K2O, 8 mol% MgO, 20 mol% CaO, 25 mol% SiO2, 30.5 mol% B2O3, 2 mol% P2O5 and 0.5 mol% CuCl2 were weighed in molar percentage to obtain the raw materials of each component. The preparation process is as follows: the above materials are mixed in a platinum crucible; calcined at 1300 ℃ for 2 h to a molten state, then taken out and poured into ice water for quenching and cooling; dried at 60 ℃ for 24 h; the dried glass is put into a ball mill at a speed of 400 rpm for 4 h, passed through a 380 mesh sieve, and a glass powder with a diameter of less than 40 μm is obtained, which is bagged and sealed to prevent moisture.

[0045] Preparation of 3D printing slurry: According to the mass percentage, 10% copper-containing borosilicate bioactive glass, 87% photosensitive resin TMPTA, 2% dispersant VOK-Disper 85000 and 1% photoinitiator 819 were mixed and placed in an agate ball mill, and then an equal mass of zirconium oxide ball milling beads (the size of the ball milling beads is 10 mm) were added, and then ball milled in a planetary ball mill for 6 hours to fully mix the raw materials of each component, and then the ball milling jar was taken out, and the ball milling beads were filtered out through a sieve, and then the materials were added to the mixing tank, and part of the air was extracted in a vacuum centrifugal mixer to achieve a negative pressure effect, and then mixed at 1000 rpm for 2 minutes. After the mixing was completed, the mixing tank was opened, and the slurry state was detected to be a paste with a smooth surface and uniform color, without bubbles, particles, etc. The obtained slurry was poured into a black light-shielding bottle to prevent natural light from solidifying the slurry, thereby preparing a DLP 3D printing slurry with a copper borosilicate bioactive glass mass percentage of 10% (the viscosity of the DLP 3D printing slurry was 3 Pa·s) and waiting for printing.

[0046] Example 2: Preparation of DLP 3D printing slurry containing 40% copper borosilicate bioactive glass by mass Preparation of copper-containing borosilicate bioactive glass: 6 mol% Na2O, 8 mol% K2O, 8 mol% MgO, 20 mol% CaO, 25 mol% SiO2, 30.5 mol% B2O3, 2 mol% P2O5 and 0.5 mol% CuCl2 were weighed in molar percentage to obtain the raw materials of each component. The preparation process is as follows: the above materials are mixed in a platinum crucible; calcined at 1300 ℃ for 2 h to a molten state, then taken out and poured into ice water for quenching and cooling; dried at 60 ℃ for 24 h; the dried glass is put into a ball mill at a speed of 400 rpm for 4 h, passed through a 380 mesh sieve, and a glass powder with a diameter of less than 40 μm is obtained, which is bagged and sealed to prevent moisture.

[0047] Preparation of 3D printing slurry: According to the mass percentage, 40% copper-containing borosilicate bioactive glass, 57% photosensitive resin TMPTA, 2.5% dispersant VOK-Disper 85000 and 0.5% photoinitiator 819 were mixed and placed in an agate ball mill. Then, an equal mass of zirconium oxide ball milling beads (the size of the ball milling beads was 10 mm) were added, and then ball milled in a planetary ball mill for 6 h to fully mix the raw materials of each component. After that, the ball milling jar was taken out, the ball milling beads were filtered out through a sieve, and the obtained slurry was poured into a black light-shielding bottle to prevent natural light from solidifying the slurry. In this way, a DLP 3D printing slurry with a mass percentage of 40% copper-containing borosilicate bioactive glass was prepared (the viscosity of the DLP 3D printing slurry was 5 Pa·s), and then it was prepared for printing.

[0048] Example 3: Preparation of DLP 3D printing slurry containing 70% copper borosilicate bioactive glass by mass Preparation of copper-containing borosilicate bioactive glass: 6 mol% Na2O, 8 mol% K2O, 8 mol% MgO, 20 mol% CaO, 25 mol% SiO2, 30.5 mol% B2O3, 2 mol% P2O5 and 0.5 mol% CuCl2 were weighed in molar percentage to obtain the raw materials of each component. The preparation process is as follows: the above materials are mixed in a platinum crucible; calcined at 1300 ℃ for 2 h to a molten state, then taken out and poured into ice water for quenching and cooling; dried at 60 ℃ for 24 h; the dried glass is put into a ball mill at a speed of 400 rpm for 4 h, passed through a 380 mesh sieve, and a glass powder with a diameter of less than 40 μm is obtained, which is bagged and sealed to prevent moisture.

[0049] Preparation of 3D printing slurry: According to the mass percentage, 70% copper-containing borosilicate bioactive glass, 26.7% photosensitive resin TMPTA, 3% dispersant VOK-Disper 85000 and 0.3% photoinitiator 819 were mixed and placed in an agate ball mill. Then, an equal mass of zirconium oxide ball milling beads (the size of the ball milling beads was 10 mm) were added, and then ball milled in a planetary ball mill for 6 h to fully mix the raw materials of each component. After that, the ball milling jar was taken out, the ball milling beads were filtered out through a sieve, and the obtained slurry was poured into a black light-shielding bottle to prevent natural light from solidifying the slurry. In this way, a DLP 3D printing slurry with a mass percentage of 70% copper-containing borosilicate bioactive glass was prepared (the viscosity of the DLP 3D printing slurry was 7 Pa·s), and then it was prepared for printing.

[0050] Example 4: Preparation of DLP 3D printing slurry containing 60% copper borosilicate bioactive glass by mass Preparation of copper-containing borosilicate bioactive glass: 6 mol% Na2O, 8 mol% K2O, 8 mol% MgO, 20 mol% CaO, 25 mol% SiO2, 30.5 mol% B2O3, 2 mol% P2O5 and 0.5 mol% CuCl2 were weighed in molar percentage to obtain the raw materials of each component. The preparation process is as follows: the above materials are mixed in a platinum crucible; calcined at 1300 ℃ for 2 h to a molten state, then taken out and poured into ice water for quenching and cooling; dried at 60 ℃ for 24 h; the dried glass is put into a ball mill at a speed of 400 rpm for 4 h, passed through a 380 mesh sieve, and a glass powder with a diameter of less than 40 μm is obtained, which is bagged and sealed to prevent moisture.

[0051] Preparation of 3D printing slurry: According to the mass percentage, 60% copper-containing borosilicate active glass, 37% photosensitive resin TMPTA, 2.5% dispersant VOK-Disper 85000 and 0.5% photoinitiator 819 were mixed and placed in an agate ball mill. Then, an equal mass of zirconia ball milling beads (the size of the ball milling beads was 10 mm) were added, and then ball milled in a planetary ball mill for 6 h to fully mix the raw materials of each component. After that, the ball milling jar was taken out, the ball milling beads were filtered out through a sieve, and the obtained slurry was poured into a black light-shielding bottle to prevent natural light from solidifying the slurry. In this way, a DLP 3D printing slurry with a mass percentage of 60% copper-containing borosilicate bioactive glass was prepared (the viscosity of the DLP 3D printing slurry was 8 Pa·s), and then it was prepared for printing.

[0052] Example 5: Preparation of DLP 3D printing slurry containing 60% copper borosilicate bioactive glass by mass Preparation of copper-containing borosilicate bioactive glass: 6 mol% Na2O, 8 mol% K2O, 8 mol% MgO, 20 mol% CaO, 25 mol% SiO2, 30 mol% B2O3, 2 mol% P2O5 and 1 mol% CuCl2 were weighed in molar percentage to obtain the raw materials of each component. The preparation process is as follows: the above materials are mixed in a platinum crucible; calcined at 1300 ℃ for 2 h to a molten state, then taken out and poured into ice water for quenching and cooling; dried at 60 ℃ for 24 h; the dried glass is put into a ball mill at a speed of 400 rpm for 4 h, passed through a 380 mesh sieve, and a glass powder with a diameter of less than 40 μm is obtained, which is bagged and sealed to prevent moisture.

[0053] Preparation of 3D printing slurry: According to the mass percentage, 60% copper-containing borosilicate active glass, 37% photosensitive resin TMPTA, 2.5% dispersant VOK-Disper 85000 and 0.5% photoinitiator 819 were mixed and placed in an agate ball mill. Then, an equal mass of zirconium oxide ball milling beads (the size of the ball milling beads was 10 mm) were added, and then ball milled in a planetary ball mill for 6 h to fully mix the raw materials of each component. After that, the ball milling jar was taken out, the ball milling beads were filtered out through a sieve, and the obtained slurry was poured into a black light-shielding bottle to prevent natural light from solidifying the slurry. In this way, a DLP 3D printing slurry with a mass percentage of 60% copper-containing borosilicate bioactive glass was prepared (the viscosity of the DLP 3D printing slurry was 9 Pa·s), and then it was prepared for printing.

[0054] Comparative Example 1: Preparation of DLP 3D printing slurry without copper Preparation of borosilicate bioactive glass: 6 mol% Na2O, 8 mol% K2O, 8 mol% MgO, 20 mol% CaO, 25 mol% SiO2, 31 mol% B2O3, and 2 mol% P2O5 were weighed in molar percentage to obtain the raw materials of each component. The preparation process is as follows: the above materials are mixed in a platinum crucible; calcined at 1300 °C for 2 h to a molten state, then taken out and poured into ice water for quenching and cooling; dried at 60 °C for 24 h; the dried glass is put into a ball mill at a speed of 400 rpm for 4 h, passed through a 380 mesh sieve, and a glass powder with a diameter of less than 40 μm is obtained, which is bagged and sealed to prevent moisture.

[0055] Preparation of 3D printing slurry: According to the mass percentage, 60% borosilicate bioactive glass, 37% photosensitive resin TMPTA, 2.5% dispersant VOK-Disper 85000 and 0.5% photoinitiator 819 were mixed and placed in an agate ball mill. Then, an equal mass of zirconia ball milling beads (the size of the ball milling beads was 10 mm) were added, and then ball milled in a planetary ball mill for 6 hours to fully mix the raw materials of each component. After that, the ball milling jar was taken out, the ball milling beads were filtered out through a sieve, and the obtained slurry was poured into a black light-shielding bottle to prevent natural light from solidifying the slurry. In this way, a DLP 3D printing slurry with a mass percentage of 60% borosilicate bioactive glass was prepared and waited for printing.

[0056] Example 6: Preparation of porous scaffolds DLP printing process: First, using Solidworks software, according to the pre-designed structural parameters, based on the concept of bionic human bone structure support, a hollow cylindrical porous support structure was designed, and the STL file containing the porous support structure information was sliced ​​and imported into the USB flash drive. After the above-prepared 3D printing slurry is mixed, an appropriate amount is poured into the printer material tray, the USB flash drive is inserted into the 3D printer, the set structure is selected, the 3D printer is operated, and the printing parameters of the 3D printer are set as follows: light intensity 10000μw, scraper displacement speed 100mm / s, layer-by-layer curing time 20s, layer spacing 0.5 mm, layer height 0.08 mm. Start printing, the printing platform gradually descends, contacts the slurry, starts to solidify layer by layer, and slowly accumulates on the molding platform until the printing reaches the set support height, and the printing is completed. After that, remove the molding platform, carefully scrape off the blank support on the molding platform with a knife, put on gloves, wash off the residual slurry on the blank support with alcohol, and then blow dry the alcohol with an air pump.

[0057] In order to study the optimal sintering process of the green body bracket, the green body bracket printed by the 3D printing slurry of Example 4 was subjected to thermogravimetric and differential scanning calorimetric analysis. The processing results are as follows: Figure 1 See Figure 1 From the TG curve, it can be seen that when the temperature rises to 500 ℃, the mass of the green body bracket basically does not change; combined with the DTG curve, it can be seen that when the temperature is in the range of 300 ℃~500 ℃, the weight loss rate of the green body bracket is the fastest. Therefore, when designing the sintering program, the temperature can be slowly increased in this temperature range and kept at the high temperature platform for a long time to achieve the purpose of removing the photosensitive resin to a greater extent. Based on this, the green body bracket degreasing sintering program is as follows Figure 2 shown.

[0058] The 3D printing slurries of Examples 1 to 5 were respectively printed out into green body brackets according to the above-mentioned DLP printing process. After several batches of green body brackets were printed, the holes blocked by the slurry were cleared with a needle, placed on a ceramic plate, and placed in a muffle furnace for sintering. Sintering process: starting from room temperature, the temperature was raised to 300°C at 2°C / min, and then the weight loss was relatively fast, so the heating rate was reduced, and the temperature was continued to rise to 500°C at a rate of 1°C / min, and then kept warm for 90 minutes. At this time, the weight loss process was basically completed, and the temperature was lowered in an orderly manner at a rate of 1°C / min to prevent the bracket from cracking due to sudden cooling. After it dropped to 300°C, the sintering procedure was terminated, and the porous bracket was allowed to cool naturally to room temperature to obtain a porous bioactive glass bionic bone bracket.

[0059] The results show that the four 3D printing slurries of Examples 1 to 5 can all achieve 3D printing. The porous scaffold obtained in Example 4 has a porosity of 61.5%, an average pore diameter of 315 μm, and an internal connectivity of 98.7%.

[0060] The porous scaffold prepared by the 3D printing slurry of Example 4 was characterized and tested.

[0061] (1) Morphological characterization: The SEM images of the porous scaffold prepared in Example 4 before and after sintering are as follows: Figure 3 As shown, from Figure 3 It can be seen that the green body bracket has uniform pores, smooth texture, and uniform particle distribution, which reflects the uniformity of the prepared 3D printing slurry. The microscopic morphology of the green body bracket after sintering is also uniform in pore size and uniform in distribution. The slight texture on the surface may be caused by the volume shrinkage of the material due to the removal of the organic phase of the material at high temperature. Figure 3 The results show that the present invention can effectively remove bubbles in the printing slurry through the vacuum centrifugal treatment method, thereby improving the uniformity of the printing ink and improving the quality of the porous scaffold.

[0062] (2) Mechanical testing: The experiment used a microcomputer-controlled electronic universal testing machine with displacement control and a speed of 1mm / min. Five samples were tested in each group. The deformation of the porous bracket was set to be greater than 15% as the failure mechanism. The compressive strength was calculated based on the measured compressive area and the maximum load at failure. The curve is shown in the figure. Figure 4 The results show that the compressive strength of the porous scaffolds containing 60% copper borosilicate bioactive glass is maintained at about 4 MPa, indicating that the porous scaffolds prepared by the present invention have a certain mechanical strength and can meet the subsequent transplantation requirements for bone repair in non-load-bearing parts.

[0063] (3) Cytotoxicity: The cell culture medium of human bone marrow mesenchymal stem cells (hBMSCs) was used to extract the porous scaffold. The volume of the cell culture medium was based on the national medical device standard. The mass ratio of the columnar porous scaffold to the volume of the extract was 0.2 g / mL. The porous scaffold and the corresponding cell culture medium were placed in a 15 mL centrifuge tube, sealed and placed in a 37 °C shaker for 1 day. After that, the porous scaffold was taken out, and the cell culture medium was filtered with a sterile filter membrane to remove impurities and bacteria to obtain the extract. Finally, a gradient dilution of the porous scaffold extract was prepared, with a total of ten groups, namely, cell culture medium (control), extract, and extract diluted 2 times, 4 times, 8 times, 16 times, 32 times, 64 times, 100 times, and 128 times, and then added to the corresponding well plates, and then continued to be placed in the incubator for culture.

[0064] Prepare a sufficient amount of 90% serum-free culture medium (containing 1% double antibody) and 10% CCK-8 detection reagent mixture, add it to the well plate, then put it in the incubator under light protection, wait for 2 hours and then put it in the UV spectrophotometer to measure the absorbance. The results of the cytotoxicity experiment of bone marrow mesenchymal stem cells are shown in the figure. Figure 5 As shown, the extract and its serial dilutions all showed high cell activity, with a cell activity decrease of less than 30%, meeting the non-toxic standard. The gradient dilutions all showed no obvious toxicity.

[0065] (4) Effect of copper-containing porous scaffold extract on hBMSCs osteogenic gene transcription The porous scaffold extracts of Example 4, Example 5 and Comparative Example 1 were prepared in the same manner as above. After diluting each porous scaffold extract by 16 times, osteogenic induction factors were added to induce the culture of hBMSCs cells to form three experimental groups, namely, Experimental Group 1 of Comparative Example 1 without copper, Experimental Group 2 of Example 4 containing 0.5 mol% copper, and Experimental Group 3 of Example 5 containing 1 mol% copper. α-MEM osteogenic induction medium was used as a blank control group. The mRNA transcription levels of related genes (ALPL, COL1A1, Runx2, ocn, opn and sp7 genes) were detected at 14 days of induction culture, and the results are shown in the figure. Figure 6 shown.

[0066] from Figure 6 It can be seen that after the 14th day of induction culture, the gene expression of each experimental group was higher than that of the blank control group. The expression of the Runx2 gene in experimental group 2 containing 0.5 mol% copper and experimental group 3 containing 1 mol% copper was particularly obvious, far exceeding the blank control group and experimental group 1 without copper ion doping. This shows that copper ions are beneficial to the expression of the Runx2 gene; for genes such as Alpl, Ocn, and Sp7, the gene expression levels of the experimental groups were greater than those of the blank control group, and as the copper ion content increased, the expression levels increased accordingly. This shows that copper ions have a promoting effect on the expression of these osteogenic genes, and the higher the content within a certain range, the better the promotion effect.

[0067] It can be seen from the above data that the porous scaffold prepared by the present invention using copper-containing bioactive glass organisms as the main raw material has low toxicity. More importantly, the use of copper-containing bioactive glass organisms in the present invention introduces copper ions into the DLP 3D printing slurry, promotes the expression of cell osteogenesis-related genes, promotes local vascularization and regulates inflammation to achieve osteogenesis regeneration, and has a certain promoting effect on bone repair. In addition, in the preparation method of the DLP 3D printing slurry of the present invention, a vacuum centrifugal treatment method is adopted, which makes it easier to remove bubbles in the slurry, improve the uniformity of the printing ink, and improve the quality and purity of the porous scaffold.

Claims

1. A DLP 3D printing slurry, characterized in that: Calculated by mass percentage, it includes: 10%~70% copper-containing bioactive glass, 26.7%~87% photosensitive resin, 0.3%~1% photoinitiator, and 2%~3% dispersant.

2. The DLP 3D printing slurry according to claim 1, characterized in that: The copper-containing bioactive glass is copper-containing borosilicate bioactive glass; in terms of molar percentage, the proportion of copper in the copper-containing borosilicate bioactive glass is 0.1% to 1%.

3. The DLP 3D printing slurry according to claim 1, characterized in that: The photosensitive resin is trimethyl isopropyl phenol vinyl ester.

4. The DLP 3D printing slurry according to claim 1, characterized in that: The viscosity of the DLP 3D printing slurry is 2-10 Pa·s.

5. The method for preparing the DLP 3D printing slurry according to any one of claims 1 to 4, characterized in that: include: (1) uniformly mixing a photoinitiator, a photosensitive resin, a copper-containing bioactive glass and a dispersant to obtain a mixed solution; (2) The mixed liquid is subjected to vacuum centrifugation to obtain DLP 3D printing slurry.

6. The method for preparing DLP 3D printing slurry according to claim 5, characterized in that: The vacuum centrifugation treatment time is 10 to 120 s.

7. A porous stent, characterized in that: The DLP 3D printing slurry according to any one of claims 1 to 4 is used as a raw material and printed by a DLP 3D printing method.

8. The method for preparing the porous scaffold according to claim 7, characterized in that: include: (1) setting DLP 3D printing parameters, and forming the DLP 3D printing slurry by DLP 3D printing to obtain a bracket blank; (2) Sintering the scaffold blank at 500-850 °C to obtain a porous scaffold.

9. The method for preparing a porous scaffold according to claim 8, characterized in that: In step (2), the sintering procedure is: heating to 280~320°C at a rate of 1.8~2.2°C / min, continuing to heat to 500~850°C at a rate of 0.8~1.2°C / min, keeping the temperature for 80~100 min, and then cooling to 280~320°C at a rate of 0.8~1.2°C / min.

10. Use of the porous scaffold according to claim 7 in preparing bone repair materials.

Citation Information

Patent Citations

  • Novel multifunctional mesoporous glass bracket with biological activity as well as preparation method and purpose thereof

    CN103721292A

  • High-strength bioactive glass bracket and 3D printing method thereof

    CN114455834A

  • Bone repair material as well as preparation method and application thereof

    CN117679557A

  • Nano-cement comprising copper-doped bioactive glass nanoparticle, and preparing method therefor

    WO2021112515A2